Synthesis of Organo-Montmorillonite/Sodium Alginate Graft Poly(Acrylic Acid -Co-2-Acrylamido-2-Methyl-1-Propane Sulfonic Acid) Superabsorbent Composite and Its Adsorption Studies. Issue 4 (May 2014) - Zhu, Linhui; Zhang, Lili; Tang, Yaoji
A new superabsorbent composite based on the natural material sodium alginate (SA) was synthesized by intercalation graft polymerization of SA, acrylic acid (AA), 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS) and organo-montmorillonite (OMMT) using ammonium persulfate (APS) as an initiator and N, N'-methylenebisacrylamide (MBA) as a cross linker. The composite was characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA), and was used to remove heavy metal ions such as Pb 2+, Ni 2+ and Cu 2+ from aqueous solutions. Maximum adsorption capacities for Pb 2+, Ni 2+ and Cu 2+ were 1485, 303 and 294 mg/g respectively. It was found that the adsorption of Pb 2+ was consistent with both the Langmuir and the Freundlich model, while that of Ni 2+ and Cu 2+ was in accordance with the Langmuir model. Mechanisms for the adsorption process were speculated upon. It revealed that chelation was dominant for the adsorption of Pb 2+, while ion-exchange played an important role for adsorption of Ni 2+ and Cu 2+ . The superabsorbent composite had good reuse performance in wastewater treatment.